Erythromycin treatment hinders the induction of oral tolerance to fed ovalbumin - Lambert, Sydney E.; Kinder, Jeremy M.; Then, Jenny E.; Parliament, Kelly N.; Bruns, Heather A. (Frontiers in Immunology, 2012)
The mucosal immune system is constantly exposed to antigen, whether it be food antigen, commensal bacteria, or harmful antigen. It is essential that the mucosal immune system can distinguish between harmful and non-harmful antigens, and initiate an active immune response to clear the harmful antigens, while initiating a suppressive immune response (tolerance) to non-harmful antigens. Oral tolerance is an immunologic hyporesponsiveness to an orally administered antigen and is important in preventing unnecessary gastrointestinal (GI) tract inflammation, which can result in a number of autoimmune and hypersensitivity diseases. Probiotics (beneficial intestinal bacteria), T regulatory cells (Tregs), and dendritic cells (DCs) are all essential for generating tolerance. Antibiotics are commonly prescribed to fight infections and often necessary for maintaining health, but they can disrupt the normal intestinal probiotic populations. There is increasing epidemiologic evidence that suggests that antibiotic usage correlates with the development of atopic or irritable bowel disorders, which often result due to a breakdown in immune tolerance. This study investigated the effect of the antibiotic erythromycin on oral tolerance induction to ovalbumin (OVA). The results demonstrated that antibiotic treatment prior to exposure to fed antigen prevents tolerance to that antigen, which may be associated with a reduction in intestinal Lactobacillus populations. Furthermore, antibiotic treatment resulted in a significant decrease in the tolerogenic CD11c+/CD11b+/CD8α- MLN DCs independent of tolerizing treatment. These results provide evidence that antibiotic treatment, potentially through its effects on tolerogenic DCs and intestinal microflora, may contribute to autoimmune and atopic disorders via a breakdown in tolerance and support prior epidemiologic studies correlating increased antibiotic usage with the development of these disorders.